2022
DOI: 10.1038/s12276-022-00734-y
|View full text |Cite
|
Sign up to set email alerts
|

TRIM45 causes neuronal damage by aggravating microglia-mediated neuroinflammation upon cerebral ischemia and reperfusion injury

Abstract: Excessive and unresolved neuroinflammation is a key component of the pathological cascade in brain injuries such as ischemic stroke. Tripartite motif-containing 45 (TRIM45) is a ubiquitin E3 ligase involved in various critical biological processes. However, the role of TRIM45 in cerebral ischemia remains unknown. Here, we found that the TRIM45 protein was highly expressed in the peri-infarct areas of mice subjected to cerebral ischemia and reperfusion injury induced by middle cerebral artery occlusion. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…The spatial learning and memory of the mice were determined by the MWM test as described previously [ 34 ]. Briefly, the water maze consists of a circular tank with a diameter of 120 cm and a circular platform with a diameter of 6 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The spatial learning and memory of the mice were determined by the MWM test as described previously [ 34 ]. Briefly, the water maze consists of a circular tank with a diameter of 120 cm and a circular platform with a diameter of 6 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we investigated the protective effects of SENP6 knockdown on cerebral ischaemia in vivo. First, we applied an adeno-associated virus type 2/6 (AAV2/6)-mediated approach to knockdown SENP6 in microglia in the brains of ischaemic mice [ 19 , 20 , 24 ]. For this, we constructed AAV2/6, which expresses shRNA only in cells expressing Cre recombinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intraluminal filament technique was used to induce focal cerebral ischaemia through the transient occlusion of the middle cerebral artery as we reported previously [ 20 ]. In brief, mice were anaesthetized using chloral hydrate (350 mg/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was demonstrated that TRIM45 regulates cerebral I/R injury by activating NF-κB signaling in microglia through interaction with TAB2, consequently leading to neuronal apoptosis. Knockdown of TRIM45 has proved to provide striking results for the above effects by inhibiting the inflammatory response [ 72 ].…”
Section: Trim Proteins and The Nervous System: Insights Into Brain Ph...mentioning
confidence: 99%